Optimización del uso de ampicilina/sulbactam, piperacilina/tazobactam y caspofungina del Hospital Víctor Lazarte Echegaray, abril 2017-marzo 2019 - Inga Borjas, Wendy Luz (2019)
This report of pre-professional practices, aims to compare the consumption of medications, before and after the implementation of the PROA Antimicrobial Optimization Program at Víctor Lazarte Echegaray Hospital, april 2017-march 2019. The sample consisted of patients hospitalized in the department of medicine and surgery B. The method used was the international technique of Defined Daily Dose, by which the DDD / 100stays / day of ampicillin was evaluated 1 g / sulbactam 0.5 g, piperacillin 4 g / tazobactam 0.5 g and caspofungin 50 mg. The results of DDD / 100 stay / day before the implementation of the program in the services of medicine and surgery B, were for ampicillin / sulbactam of 2.105 and 0.860, piperacillin / tazobactam of 6.863 and 0.984 and caspofungin of 1.637 and 0.323; while the results of DDD / 100 stay / day after the implementation of the program in the services of medicine and surgery B, were for ampicillin / sulbactam of 1.164 and 0.530, piperacillin / tazobactam of 3.959 and 0.724 and caspofungin of 0.968 and 0.123. By means of the percentage variation test, a decrease was demonstrated in comparison to the before and after, of the implementation of the program, the percentage values found by this test in the medical service were 44%, 42% and 40% and in the service of surgery B were 38%, 26% and 61% respectively for each antibiotic. It was concluded that with the implementation of the PROA a percentage decrease in the consumption of ampicillin / sulbactam, piperacillin / tazobactam and caspofungin was achieved in the medical and surgical services B.